MiR-181c-BRK1 axis plays a key role in actin cytoskeleton-dependent T cell function. Issue 5 (14th April 2018) - Lim, Shok Ping; Ioannou, Nikolaos; Ramsay, Alan G; Darling, David; Gäken, Joop; Mufti, Ghulam J
Abstract: MicroRNAs are short endogenous noncoding RNAs that play pivotal roles in a diverse range of cellular processes. The miR-181 family is important in T cell development, proliferation, and activation. In this study, we have identified BRK1 as a potential target of miR-181c using a dual selection functional assay and have showed that miR-181c regulates BRK1 by translational inhibition. Given the importance of miR-181 in T cell function and the potential role of BRK1 in the involvement of WAVE2 complex and actin polymerization in T cells, we therefore investigated the influence of miR-181c -BRK1 axis in T cell function. Stimulation of PBMC derived CD3 + T cells resulted in reduced miR-181c expression and up-regulation of BRK1 protein expression, suggesting that miR-181c -BRK1 axis is important in T cell activation. We further showed that overexpression of miR-181c or suppression of BRK1 resulted in inhibition of T cell activation and actin polymerization coupled with defective lamellipodia generation and immunological synapse formation. Additionally, we found that BRK1 silencing led to reduced expressions of other proteins in the WAVE2 complex, suggesting that the impairment of T cell actin dynamics was a result of the instability of the WAVE2 complex following BRK1 depletion. Collectively, we demonstrated that miR-181c reduces BRK1 protein expression level and highlighted the important role of miR-181c -BRK1 axis in T cell activation and actin polymerization-mediated T cell functions. Abstract : miR-181c modulates actin polymerization-mediated T cell functions by regulating BRK1.